Effect of Drying Temprature on some Properties of Polymer Composite with Epoxy K-153 Matrix - Nguyen, Trung Thanh (H. : ĐHQGHN, 2020)
The article introduces the effects of drying temperature on curing level, thermal endurance, thermal oxidation resistance, surface structure morphology of polymer composite material based on K-153 epoxy resin (K-153 epoxy resin is made from ED-20 epoxy resin modified by thiokol and oligomer acrylate), T-13 glass fiber and hardener polyethylenepolyamine. The results show that the thermal endurance, thermal oxidation resistance, surface structure morphology of polymer composite change much when the drying temperature changes. When the drying temperature increases from 60°C to about 80°C, the structure of the polymer composites are tighter, the thermal endurance, thermal oxidation resistance also increases, however, if the drying temperature is continued to increase, these properties of the material will reduce.